The theology of Martin Luther King Jr. and Desmond Mpilo Tutu - Hill, Johnny B. (Black religion, womanist thought, social justice., 2007)
Johnny B. Hill brings two of the most prominent theologians of our time, Martin Luther King Jr. and Desmond Tutu, into conversation to explore the meaning of the Christian ideas of reconciliation, multiculturalism, and social justice for today?s world. This new work offers a comprehensive analysis of King and Tutu?s theology with implications for contemporary issues.